Machine learning based cloud computing intrusion detection - Isong, Akwaeno; Utibe-Abasi Stephen, Bliss; Asuquo, Philip; Ihemereze, Chijioke; Enang, Imoh (Національний технічний університет "Харківський політехнічний інститут", 2026)
Based on today’s technologically networked world, a sophisticated networking technology known as Software-Defined Networking (SDN) is utilized in cloud computing environments to improve the effectiveness of network management. However, SDN’s centralized nature makes it vulnerable to DDoS attacks. This study introduces a technique for detecting DDoS attacks within a cloud computing setting. The research seeks to apply an ensemble machine learning approach for statistically identifying DDoS attacks in cloud network traffic, categorizing them as either harmful or harmless. Various machine learning algorithms, including K-Nearest Neighbors, Random Forest (RF), and Decision Tree, were utilized as foundational classifiers in the suggested ensemble machine learning model. A dataset of SDN–DDoS attacks was utilized to assess the efficacy of the base classifiers. The classifiers were trained using 80% of the dataset and evaluated on 20%. The results of the experiment indicated that the Random Forest and Random Forest classifiers attained 100% accuracy, whereas the K-Nearest Neighbor classifier achieved an accuracy of 98.21%. The ensemble machine learning model employed a majority voting technique for final prediction and achieved an accuracy of 100% on the test set, ranking as the best compared to benchmark models.

В умовах сучасного технологічно поєднаного світу у хмарних обчислювальних середовищах використовується передова мережева технологія, відома як програмно-конфігуровані мережі (SDN), щоб підвищити ефективність управління мережею. Однак централізована природа SDN робить її вразливою до DDoS-атак. У цьому дослідженні представлено метод для виявлення DDoS-атак у середовищі хмарних обчислень. Дослідження спрямоване на застосування ансамблевого підходу машинного навчання для статистичного розпізнавання DDoS-атак у хмарному мережевому трафіку, класифікуючи їх як шкідливі або нешкідливі. Різні алгоритми машинного навчання, включаючи K-ближчих сусідів, випадковий ліс (RF) та дерево рішень (DT), були використані як базові класифікатори в запропонованій ансамблевій моделі машинного навчання. Для оцінки ефективності базових класифікаторів було використано набір даних SDN–DDoS-атак. Класифікатори були навчені на 80% даних і протестовані на 20%. Результати експерименту показали, що класифікатори RF та DT досягли точності 100%, тоді як класифікатор K-ближчих сусідів забезпечив точність 98,21%. Ансамблева модель машинного навчання застосувала метод більшості голосів для фінального прогнозу та досягла точності 100% на тестовому наборі, ставши найкращою порівняно з еталонними моделями.
Машинне навчання для виявлення вторгнень у хмарних обчисленнях
Keywords: cloud computing; attack classification; machine learning; threat detection; intrusion detection system; artificial intelligence; deep learning; feature selection; classification algorithms; anomaly detection; хмарні обчислення; класифікація атак; машинне навчання; виявлення загроз; штучний інтелект; глибоке навчання; IaaS; PaaS; SaaS; відбір ознак; виявлення аномалій